PENINGKATAN EFEKTIVITAS SEKOLAH MELALUI PENGEMBANGAN EFIKASI DIRI GURU DAN IKLIM SEKOLAH - Rosna Wati; Nandang Hidayat; Hari Muharam (JURNAL MANAJEMEN PENDIDIKAN, 2022)
IMPROOVING SCHOOL EFFECTIVENESS THROUGH THE DEVELOPMENT OF TEACHER SELF-EFFICACY AND SCHOOL CLIMATEThis research was intended to reveal whether teacher self-efficacy and school climate have a relationship with school effectiveness. The research used a correlational research method. Data collection was carried out on 83 private vocational school teachers in Ciawi. Data analysis was performed using inferential statistics using SPSS version 22.0. The research results were concluded based on statistical analysis and  resulted in 3 conclusions; 1) there was a positive relationship between self-efficacy (X1) and school effectiveness (Y). The correlation coefficient (ry1) was 0.076, and self-efficacy contributed 0.58% of the increasing in school effectiveness. 2) There was a positive relationship between school climate (X2) and school effectiveness (Y). The correlation coefficient (ry2) was 0.905, and the school climate contributed 81.9% to the increasing of school effectiveness. 3) There was a positive relationship between self-efficacy (X1) and school climate (X2) altogether to school effectiveness (Y). The correlation coefficient (ry1.2) was 0.998. The self-efficacy and school climate altogether contributed 99.5%  of school effectiveness. Based on these findings, it could be concluded that school effectiveness might  be increased by improving self-efficacy and school climate.